(untitled) (Economics and region, 2021)
It was proved that the effectiveness of HR management in Ukrainian banks remains extremely low compared to most developed countries in the West. It was found that the average labor productivity of employees in Ukraine is only a third of the same figure in the United States, and many times lower than labor productivity in Northern Europe and Japan. The authors analyzed the JSC “PrivatBank” activities and identified features of the HR-management implementation. The study showed that JSC “PrivatBank” despite the economic crisis, the coronavirus pandemic, the conduct of hostilities in the eastern part of Ukraine occupies a leading position in the market in our country. The analysis revealed that PrivatBank actively hires students, young people who have minimal or no work experience, but after working for a short time, young people change jobs. Specialists are moving to competitors because of higher wages and better employee motivation. It was found that employees working in the bank remain not out of loyalty to the bank, as management may mistakenly believe, but out of fear of losing their job in the new economic environment. An anonymous survey allowed us to determine how employees feel about existing methods of motivation and their expectations. The analysis showed that the management of JSC “PrivatBank” should pay attention to the implementation of new approaches to personnel management. Moreover, due to globalization, modern managers have the opportunity to objectively assess the advantages and disadvantages of each management style and try to transform their positive features to ensure the sustainable development of the banking institution. It was proved that the task of the manager is to develop and implement the company’s strategy, select competent employees, give them their own range of powers that corresponds to their competence, motivate them to make independent decisions within this range, as well as control. It was proposed to implement the Harzburg management model and identify the benefits for JSC “PrivatBank” in its application.